Pronominalization of social actors on universities’ websites: effectiveness and constitutiveness from a critical discourse analysis perspective - Tharmalingam, Selvarajah; Al-Wedyan, Ali M. (Macrothink Institute, 2016)
Discursive construction of staff identities at universities’ websites is deliberately created to categorically identify the staff according to their positions. The constructions of these identities are normally implicit in nature. The study attempts to identify the power relations with regard to the ‘WE’ and ‘I’ dichotomy in discourse from a Critical Discourse Analysis (CDA) perspective. In addition, corpus techniques also aided this study to find the collocates of these two pronouns. Transitivity analysis was conducted to categorise processes associated with each pronoun. So, the processes associated with each pronoun are a way of identifying the role played at the institution level. The focus was on specific personal pronouns ‘We’ and ‘I’ for their use, mainly, as inclusive and exclusive strategies. The data was collected from international universities’ websites. The text was selected from the ‘welcome note/letter’ by Rectors, Vice Rectors, Chancellors, Vice Chancellors, and Presidents. The universities selected for this study are from various geographical areas, namely; Universiti Science Malaysia (USM) in Malaysia, Yarmouk University (YU) in Jordan, and University of Birmingham (UB) in the United Kingdom. The analysis indicates that the use of the pronouns has a social and administrative hierarchical significance. The social actors are represented according to the specified role to play in their respective institutions.